Analysis Of Risk Factors For Stunting In Toddlers Age 12-59 Months In The Working Area The Cabangbungin Bekasi District Health Center Year 2022 - Titin Dahliawati; Titin Eka Sugiantini (Pusat Riset dan Inovasi Nasional, 2023)
Stunting is a condition of failure to thrive in toodler caused by chronic malnutrition so that children are too short for their age, as measured according to height/age indicators. Stunting has become a national problem, and is found in many developing countries, one of which is Indonesia. Stunting is caused by multiple factors. Risk factors for stunting in toddlers include birth weight, exclusive breastfeeding. parenting patterns, infectious diseases such as diarrhea and upper respiratory infections, health services and family income.The purpose of this study was to determine the risk factors for stunting in toodler. This research is a quantitative study using case-control research methods conducted in the working area of ​​the Branchbungin Public Health Center, Bekasi City. The research sample was 70 in the case and control groups. Technique of collecting data using questioner. Data analysis was performed by univariate analysis, bivariate analysis, multivariate analysis using multiple logistic regression and Population Attributable Risk (PAR) calculations with 95% confidence intervals. The results of multiple logistic regression showed that the risk factor for stunting was health services, and was the most dominant risk factor (Exp(B) = 7.334, 95% CI; 1.250-10.758). The results of the calculation of the Population Attributable Risk (PAR) for health services were 80%, meaning that the use of health services would reduce the incidence of stunting in children under five by 80%. The health workers can provide counseling about the use of under-five health services at the puskesmas as an effort to reduce the incidence of stunting in under-five children.